Shaping the discourse: What has the food industry been lobbying for in the Trans Pacific Partnership trade agreement and what are the implications for dietary health?. Issue 5 (19th October 2016) - Friel, Sharon; Ponnamperuma, Sunil; Schram, Ashley; Gleeson, Deborah; Kay, Adrian; Thow, Anne-Marie; Labonte, Ronald
Abstract: The Trans Pacific Partnership agreement (TPP), emblematic of the new generation of free trade agreements, is a regional agreement among 12 Pacific Rim countries. This paper reports on a study into how the food industry has framed issues in an effort to influence the TPP. We undertook a thematic analysis of the issues raised in publicly available submissions by the food industry to the trade negotiating bodies of four TPP countries: Australia, New Zealand, Canada and the United States of America (USA). The food industry is an active player in trade negotiations, mainly through food industry associations and other business associations. The submissions assumed that trade liberalization would result in more exports and investment, as well as raise living standards and benefit the economy and country. There was little mention of food as anything other than a commodity, focusing on types and quantities of food traded and what this meant for revenue generation, with no connection to nutritional health. The TPP could affect food systems and population health in ways that are not readily apparent to governments, policy makers or the public. The written submissions mechanism is one way in which the food industry could have shaped the agreement by framing the issues, influencing the content and direction of the TPP negotiations and agreement itself. If coherence between trade and health goals is to be strengthened, the public health community needs to engage with industry arguments and build a strong counter-argument that gives more prominence to health concerns.